Towards a lean assessment model for evaluating the maturity level of business intelligence and analytics initiatives in higher education - Cardoso, E.; Su, X. (EUNIS 2019 Congress, Proceedings, 2019)
BI and analytics market is one of the fastest growing markets in the technology segment. Currently, it is ever more relevant to periodically assess the progress of Business Intelligence (BI) initiatives in terms of delivering the expected value to business users. Although Higher Education Institutions (HEI) are seldom directly business driven, such assessment is equally relevant. There is a growing global competition for both qualified students, and the best faculty that excel both in the teaching programs and research projects. In this setting, the alignment of information systems and the business needs is key to standing out from competing HEI. Business intelligence and analytics have been instrumental for many years in delivering this alignment. However, the development of such initiatives is seldom a straightforward path. Many initiatives stall or fail for a number of reasons. It is well acknowledged that organizations that successfully deploy BI systems follow an iterative path, starting with a basic usage of data and analytical tools, and progressing to a growing sophistication of their BI applications, until the BI data-driven culture becomes embedded in the organization’s activities and decision making. The design of maturity models tries to map this progressive path, in which an organization starts with a basic or initial stage of maturity and progresses towards a more mature state. Maturity is therefore related to this notion of evolution or progression.